Regulasi Perbankan Syari’ah Pasca Lahirnya Undang-undang Nomor 21 Tahun 2008 tentang Perbankan Syari’ah (Kajian Politik Hukum) - SYAUGI MUBARAK SEFF (Jurnal Risalah Hukum, 2008)
Syari’ah economic practice actually has been widely recognized by Indonesian Moslem.However, a new positive form of this practice only begins after reformation period bythe establishment of Undang-undang Nomor 10 Tahun 1998 tentang Perubahan Undang-undangNomor 7 Tahun 1992, and Undang-undang Nomor 21 Tahun 2008 tentang Perbankan Syari’ah.Act on Syari’ah Banking has been delivered as the governmental appreciation andaccommodation to public norms (living law). Moreover, economic practice access withsyari’ah principle becomes so facilitated, and thus, any banking conventional activitiesappear being easily conducted in benefiting banks in general while preserving thecosting pattern and other issues based on syari’ah principle.Key words: regulasi (regulation), perbankan syariah (syaria’ah banking), kompetensi (competence).